Stem Cells-Loaded 3D-Printed Scaffolds for the Reconstruction of Alveolar Cleft - Luo, Dongyuan; Chen, Boying; Chen, Yu (Frontiers in Bioengineering and Biotechnology, 2022)
The advances in the field of tissue engineering and regenerative medicine have opened new vistas for the repair of alveolar clefts. However, the currently available biomaterials used for the repair of alveolar clefts have poor mechanical properties and biocompatibility, which hinders the treatment outcomes. Here, we aimed to develop 3D printed biomimetic scaffolds that fuses β-tricalcium phosphate (β-TCP) and bone marrow mesenchymal stem cells (BMSCs) for improving the repair of alveolar clefts. The methacrylate gelatin (GelMA) was mixed with β-TCP for the preparation of GelMA/β-TCP hybrid scaffolds via 3D printing platform and chemically cross-linking with UV light. The physicochemical properties of the hydrogel scaffolds were characterized. Moreover, the survival state, proliferation ability, morphological characteristics, and osteogenic induction of BMSCs were examined. The prepared hybrid scaffolds showed good biocompatibility and mechanical properties. BMSCs attached well to the scaffolds and proliferated, survived, differentiated, and stimulated osteogenesis for the reconstruction of alveolar clefts. We expect that use of the prepared hybrid hydrogel scaffold can improve the outcomes of alveolar cleft repair in clinic and expand the application of hybrid hydrogel in tissue engineering repair.